2014
DOI: 10.1016/j.ejphar.2014.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of high affinity ATP-dependent cyclic nucleotide transporters by specific and non-specific cyclic nucleotide phosphodiesterase inhibitors

Abstract: Intracellular cyclic nucleotides are eliminated by phosphodiesterases (PDEs) and by ATP Binding cassette transporters such as ABCC4 and ABCC5. PDE5 and ABCC5 have similar affinity for cGMP whereas ABCC5 has much higher affinity for cGMP compared with cAMP. Since the substrate (cGMP) is identical for these two eliminatory processes it is conceivable that various PDE inhibitors also modulate ABCC5-transport. Cyclic GMP is also transported by ABBC4 but the affinity is much lower with a Km 50-100 times higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…Studies in mammals have concluded that MTXs act through a variety of different molecular mechanisms: mobilization of intracellular calcium, inhibition of phosphodiesterases (PDEs), modulation of gamma‐amino butyric acid (GABA A ) receptors, inhibition of high affinity ATP‐dependent cyclic nucleotide transporters and antagonism of adenosine receptors . The plasma levels that could be reached under dietary regimes and the fact that MTXs readily cross the blood‐brain barrier (BBB) indicate that these drugs inhibit adenosine receptors in the central nervous system (CNS); higher doses may be required to mobilize intracellular calcium, inhibit PDEs or modulate GABA A receptors , or to unselectively inhibit ABCC5 and ABCC4 transporters . Moreover, despite the physiological relevance, also under scrutiny is how caffeine, theobromine and theophylline are able to interact with native double helical DNA .…”
Section: Health Benefits Of Methylxanthinesmentioning
confidence: 99%
“…Studies in mammals have concluded that MTXs act through a variety of different molecular mechanisms: mobilization of intracellular calcium, inhibition of phosphodiesterases (PDEs), modulation of gamma‐amino butyric acid (GABA A ) receptors, inhibition of high affinity ATP‐dependent cyclic nucleotide transporters and antagonism of adenosine receptors . The plasma levels that could be reached under dietary regimes and the fact that MTXs readily cross the blood‐brain barrier (BBB) indicate that these drugs inhibit adenosine receptors in the central nervous system (CNS); higher doses may be required to mobilize intracellular calcium, inhibit PDEs or modulate GABA A receptors , or to unselectively inhibit ABCC5 and ABCC4 transporters . Moreover, despite the physiological relevance, also under scrutiny is how caffeine, theobromine and theophylline are able to interact with native double helical DNA .…”
Section: Health Benefits Of Methylxanthinesmentioning
confidence: 99%
“…PDEs , a large family of enzymes specifically hydrolyzing the second messenger cAMP and/or cGMP, are the only cellular mechanism for degrading cAMP and cGMP [ 7 ] and thus play a critical role in regulating the intracellular levels of these second messengers and subsequently functional responses of cells [ 8 , 9 , 10 , 11 ]. The PDE9A gene encodes a cGMP-specific high-affinity PDE that seems to be widely expressed among tissues or organs in humans and mice [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…En el corazón se encuentran en mayor densidad los A 1 , en el músculo liso, los A 2B y en el endotelio, los A 2A . A concentraciones más altas, la cafeína actúa como inhibidor directo y no específico de las diferentes isoformas de la fosfodiesterasa (IC 50 : 100-1000 mM) (13). En el sistema nervioso, los receptores A 1 se expresan altamente en la corteza cerebral, el hipocampo, el cerebelo y la médula espinal; los receptores A 2A se expresan principalmente en el tubérculo olfatorio, los estriados dorsal y ventral y el plexo coroideo; los receptores A 2B y A 3 se expresan en concentraciones relativamente bajas en el cerebro (14).…”
Section: Cafeínaunclassified